Design and Synthesis of Crystalline Al-Doped TiO2 Buffer Layers for Enhancing Energy Conversion Efficiency of New Photovoltaic Devices - Dongin Kim; Jiwon Lee; Rakhyun Jeong; Ki-Hwan Hwang; Jin-Hyo Boo (Crystals)
Perovskite solar cells (PSCs) characterized by high energy conversion efficiency (ECE) and low manufacturing costs, exhibit promising potential for commercialization in the near term. For commercialization, it is very important to prevent the decomposition of perovskite by ultraviolet (UV) radiation in the air environment. Also, the mesoscopic architecture of PSCs presents considerable opportunities for the solar cell industry, offering potential for recycling of spent photocatalytic materials such as TiO2, and exploration of new energy resources. To solve these problems, therefore, this study introduces a strategy to mitigate these challenges using a crystalline Al-doped TiO2 buffer layer as the electron transport layer (ETL) in conjunction with a mesoporous TiO2 layer in the fabrication of PSCs. Among various Al concentrations in the crystalline Al-doped TiO2 buffer layer fabricated via spin-coating, an optimum concentration of 7 mol% Al yielded the highest cell performance in the specific perovskite solar cell structure. These solar cells exhibited an impressive ECE of 11.87%, representing a substantial enhancement of nearly double the ECE (6.37%) achieved with the conventional ETL. This remarkable improvement can be attributed to the passivation effect of the newly developed ETL, which combines a crystalline Al-doped TiO2 buffer layer with a mesoporousTiO2 layer. Electrochemical impedance spectroscopy (EIS) analysis was performed in conjunction with theoretical calculations of charge transport parameters to substantiate this claim.